Formulation of Isohydricity Conditions in Acid-Base systems - A Review - Anna, M. Michałowska-Kaczmarczyk; Tadeusz, Michałowski (Journal of New Developments in Chemistry, 2020)
The isohydricity conditions are formulated for D+T systems composed of titrand D and titrant T, mixed according to titrimetric mode; only acid-base equilibria are involved there. The original method of dissociation constants determination, based on the isohydricity principle, is presented and confirmed experimentally. The pH titrations in the system of isohydric solutions are also put in context with conductometric titrations.
Keywords: Isohydricity; acids; bases; pH titration; conductometric titration.